ANALISIS KELAYAKAN INSTALASI LISTRIK PADA BANGUNAN SEKOLAH DASAR NEGERI LESENG BERDASARKAN PERSYARATAN UMUM INSTALASI LISTRIK (PUIL) 2011 - MUHAMMAD ZULFAHRI FAUZAN; Nova Ariyanto; Nova Ariyanto; Ahmad Jaya; Paris Ali Topan; Desi Maulidyawati (Program Studi Teknik Elektro, 2026)
Electrical installations are essential infrastructure in educational buildings because they ensure the safe and reliable distribution of electrical energy to support teaching and learning activities. Electrical installations that have been used for many years may experience deterioration due to aging, increased electrical loads, and inadequate maintenance, thereby increasing the risk of electrical hazards such as short circuits, electric shocks, equipment failures, and fires. This study aimed to evaluate the feasibility of the electrical installation at Leseng State Elementary School based on the General Requirements for Electrical Installations (PUIL) 2011. A descriptive research method with a field observation approach was employed through visual inspection, direct measurement, documentation, and interviews. The assessment covered the condition of Miniature Circuit Breakers (MCBs), switches, socket outlets, lamp holders, conductors, cable joints, and the conformity of the installation with PUIL 2011 standards. The results indicate that several components, including switch height, socket outlet height, and supply voltage, comply with the applicable standards. However, several deficiencies were identified, including damaged MCB covers, improper conductor colour identification, cable joints without appropriate connectors, non-standard cable branching, and damaged lamp holders. Therefore, it can be concluded that the electrical installation at Leseng State Elementary School does not fully comply with the requirements of PUIL 2011 and requires corrective actions to improve its safety, reliability, and operational feasibility.